Educational Trajectories in Latin America and the Caribbean in the 21st Century (Foro de Educacion, 2021)
Inequality is a historical and structural characteristic of Latin American societies that has been maintained and reproduced even in periods of economic growth and prosperity. Although there have been important advances in the last fifteen years, Latin America and the Caribbean continues to be the most unequal region in the world. Based on the notion of social space (Bourdieu, 1979, 1989, 2002) and statistics from ECLAC (2017). The article explores the space of socioeconomic and educational differences between the twenty-five countries that make up the region. How are educational and social differences related in this set of countries? The main objective of the article is to shed light on the importance of the educational dimension in the understanding of social inequalities between these countries, described by economists, demographers and social scientists. The work presents a map of the current state of the national educational systems. At least three types of educational pathways can be distinguished: those of young people who only work, those of those who only study and those who study and work, examining the way in which the differentiation of the paths is related to inequalities social issues, particularly gender and ethnic origin.